The study of the relationship between the levels of melatonin in the blood serum and melatonin-positive-labeled cells in ulcerative lesions of the stomach in male rats of different age = Вивчення взаємозв’язку між рівнями мелатоніну в сироватці крові та мелатонін-позитивно-міченими клітинами при виразковому ураженні шлунка у щурів-самців різного віку - Hnatiuk, V. V.; Kononenko, N. M. (Journal of Education, Health and Sport, 2016)
Hnatiuk V. V., Kononenko N. M. The study of the relationship between the levels of melatonin in the blood serum and melatonin-positive-labeled cells in ulcerative lesions of the stomach in male rats of different age = Вивчення взаємозв’язку між рівнями мелатоніну в сироватці крові та мелатонін-позитивно-міченими клітинами при виразковому ураженні шлунка у щурів-самців різного віку. Journal of Education, Health and Sport. 2016;6(9):524-530. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154731 http://ojs.ukw.edu.pl/index.php/johs/article/view/3874 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. UDC 616.33-002.44-055.1: 616.155.32:612.325 THE STUDY OF THE RELATIONSHIP BETWEEN THE LEVELS OF MELATONIN IN THE BLOOD SERUM AND MELATONIN-POSITIVE-LABELED CELLS IN ULCERATIVE LESIONS OF THE STOMACH IN MALE RATS OF DIFFERENT AGE V. V. Hnatiuk, N. M. Kononenko National University of Pharmacy, Kharkiv, Ukraine Melatonin is a universal adaptogen that regulates the function of many body systems. The main source of the melatonin synthesis is the epiphysis where it is produced from the amino acid tryptophan under the control of suprachiasmatic nuclei of the hypothalamus depending on the intensity of the signal from photoreceptors of the retina. Moreover, the content of melatonin in the body is not only associated with the pineal gland secretion by pinealocytes, but with the extrapineal sources of its synthesis – the mucous membrane of the gastrointestinal tract, thymus, placenta, etc. In recent years the attention of researchers is attracted to the study of the role of melatonin in the pathogenesis of erosive and ulcerative lesions of the stomach. Therefore, the aim of our research was to study the relationship between the levels of melatonin in the blood serum and melatonin-positive-labeled cells in ulcerative lesions of the stomach in male rats of different age of 9, 15 and 20 months corresponding to the human age of 29–30, 43–44, 55–56 years, respectively. In the course of the study conducted it was found that on the background of ulcerative lesion there was a significant reduction of both the level of melatonin in the blood and the number of melatonin-positive-labeled cells in gastro mucosa. Under the influence of ulcerative lesion the number of melatonin-positive-labeled cells significantly decreased in all age groups; moreover, significant differences between the number of melatonin-positive-labeled cells in animals of different age in the experimental groups were absent. The level of melatonin in the blood serum decreased more in rats at the age of 9 and 20 months. In this time the number of melatonin-positive-labeled cells significantly decreased in rats at the age of 9 and 15 months. The greatest decrease of parameters is observed in rats at the age of 9 months, and it corresponds to the human age of 29-30 years. Keywords: melatonin, age, sex, ulcer, stomach, immunohistochemical. ВИВЧЕННЯ ВЗАЄМОЗВ’ЯЗКУ МІЖ РІВНЯМИ МЕЛАТОНІНУ В СИРОВАТЦІ КРОВІ ТА МЕЛАТОНІН-ПОЗИТИВНО-МІЧЕНИМИ КЛІТИНАМИ ПРИ ВИРАЗКОВОМУ УРАЖЕННІ ШЛУНКА У ЩУРІВ-САМЦІВ РІЗНОГО ВІКУ В. В. Гнатюк, Н. М. Кононенко Національний фармацевтичний університет, Харків, Україна Проведено дослідження рівнів мелатоніну в сироватці крові та кількості мелатонін-позитивно-мічених клітин при виразковому ураженні шлунка у щурів-самців різного віку 9, 15 та 20 міс., що відповідає віку людини 29-30, 43-44 та 55-56 років. Встановлено, що на тлі виразкового пошкодження відбувається достовірне зниження як рівня мелатоніну в крові, так і кількості мелатонін-позитивно-мічених клітин в слизовій оболонці шлунка. Під впливом виразкового ураження кількість мелатонін-позитивно-мічених клітин достовірно знижується у всіх вікових групах, при цьому достовірні відмінності між кількістю мелатонін-позитивно-мічених клітин у тварин різного віку експериментальних груп відсутні. Мелатонін в сироватці крові найбільше знижується у щурів віком 9 та 20 міс., в той час як кількість мелатонін-позитивно-мічених клітин значно зменшена у щурів віком 9 та 15 міс.. Таким чином, найбільші зниження показників спостерігаються у щурів віком 9 міс., що відповідає віку людини 29-30 років. Ключові слова: мелатонін, вік, стать, виразка, шлунок, імунногістохімія. ИЗУЧЕНИЕ ВЗАИМОСВЯЗИ МЕЖДУ УРОВНЯМИ МЕЛАТОНИНА В СЫВОРОТКЕ КРОВИ И МЕЛАТОНИН-ПОЛОЖИТЕЛЬНО-МЕЧЕНЫМИ КЛЕТКАМИ ПРИ ЯЗВЕННОМ ПОРАЖЕНИИ ЖЕЛУДКА У КРЫС САМЦОВ РАЗНОГО ВОЗРАСТА В. В. Гнатюк, Н. М. Кононенко Национальный фармацевтический университет, Харьков, Украина Проведено исследование уровней мелатонина в сыворотке крови и количества мелатонин-положительно-меченых клеток при язвенном поражении желудка у крыс-самцов разного возраста 9, 15 и 20 мес., что соответствует возрасту человека 29-30, 43-44 и 55-56 лет. Установлено, что на фоне язвенного повреждения происходит достоверное снижение как уровней мелатонина в крови, так и количества мелатонин-положительно-меченых клеток в слизистой оболочке желудка. Под влиянием язвенного поражения количество мелатонин-положительно-меченых клеток достоверно снижается во всех возрастных группах, при этом достоверные различия между количеством мелатонин-положительно-меченых клеток у животных разного возраста экспериментальных групп отсутствуют. Мелатонин в сыворотке крови больше снижается у крыс в возрасте 9 и 20 мес., в то время как количество мелатонин-положительно-меченых клеток более снижено у крыс в возрасте 9 и 15 мес. Таким образом, наибольшее снижение показателей наблюдаются у крыс в возрасте 9 мес., что соответствует возрасту человека 29-30 лет. Ключевые слова: мелатонин, возраст, пол, язва, желудок, имунногистохимия.